2009
DOI: 10.1590/s1678-91992009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and hepatotoxicity in rats induced by poisonous pufferfish (Lagocephalus lagocephalus) meat

Abstract: ABSTRACT:This study was undertaken to evaluate the effect of pufferfish (Lagocephalus lagocephalus) meat poisoning on hepatic functions of Wistar rats. For this purpose, groups of rats (Lcr, Lcu+b and Lcu-b) received diet supplemented with 10% of raw or cooked meat, respectively, with or without cooking water of L. lagocephalus while groups Mcr and Mcu+b received diet supplemented with 10% of raw or cooked meat of Liza aurata, which were used as a negative control. In Lcu+b group, ALT, AST and ALP rates (hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…injection of extract, homogenate (Zaki et al, 2001;Saoudi et al, 2011) or oral administration (Saoudi et al, 2009) of meat obtained from different (Zaki et al, 2001), decrease of serum enzyme activity (i.e. aldolase (ALS), alanine aminotransferase (ALT), alkaline phosphatase (ALP), y-glutamyl transpeptidase (GTP) and lactate dehydrogenase (LDH)), hepatic damage (increased lipid peroxidation, focal necrosis, hepatic chord, infiltration of lymphocytes, congestion in central veins and sinusoids; Saoudi et al, 2009Saoudi et al, , 2011 were observed. No information on the amount of TTX or the presence of analogues was provided.…”
Section: Acute Toxicity Studies With Ttx From Extracts and Pufferfishmentioning
confidence: 99%
See 2 more Smart Citations
“…injection of extract, homogenate (Zaki et al, 2001;Saoudi et al, 2011) or oral administration (Saoudi et al, 2009) of meat obtained from different (Zaki et al, 2001), decrease of serum enzyme activity (i.e. aldolase (ALS), alanine aminotransferase (ALT), alkaline phosphatase (ALP), y-glutamyl transpeptidase (GTP) and lactate dehydrogenase (LDH)), hepatic damage (increased lipid peroxidation, focal necrosis, hepatic chord, infiltration of lymphocytes, congestion in central veins and sinusoids; Saoudi et al, 2009Saoudi et al, , 2011 were observed. No information on the amount of TTX or the presence of analogues was provided.…”
Section: Acute Toxicity Studies With Ttx From Extracts and Pufferfishmentioning
confidence: 99%
“…Acute toxicity studies with TTX from extracts and pufferfish meat Some studies describe the toxicity induced by i.p. injection of extract, homogenate (Zaki et al, 2001;Saoudi et al, 2011) or oral administration (Saoudi et al, 2009) of meat obtained from different types of pufferfish (Lagocephalus sceleratus and Lagocephalus lagocephalus) as a source of TTX.…”
Section: Acute Studies With Pharmacological Ttx Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-exposure of metal/ metalloid mixtures of heavy metals in household and drinking water produce severe effects at both relatively high and low dose levels [31,[41][42][43][44][45][46]. This study is a brief reflection of the toxicological effects of industrialization on water resources, as well as the pharmacological effects of contaminated household and drinking water on animal model of an industrialized area in a developing country.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study (Saoudi et al, 2007), the toxicity risk of L. lagocephalus showed a disturbance in physiological and biochemical parameters in Wistar rats nourished with L. lagocephalus when compared with rats fed the diet contained a non toxic fish, the mule Liza aurata. The diet containing meat cooked with L. lagocephalus cooking water induced hepatotoxicity and oxidative stress in rats after 48 h and 2 months of treatment (Saoudi et al, 2009).…”
Section: Introductionmentioning
confidence: 98%